2021
DOI: 10.3389/fphys.2021.713048
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Lipoprotein Subfractions and Area and Density of Abdominal Muscle and Intermuscular Adipose Tissue: The Multi-Ethnic Study of Atherosclerosis

Abstract: Skeletal muscle quantity and quality decrease with older age, which is partly attributed to ectopic fat infiltration and has negative metabolic consequences. To inform efforts to preserve skeletal muscle with aging, a better understanding of biologic correlates of quantity and quality of muscle and intermuscular adipose tissue (IMAT) is needed. We used targeted lipidomics of lipoprotein subfractions among 947 Multi-Ethnic Study of Atherosclerosis participants to provide a detailed metabolic characterization of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…As a matter of fact, metabolic muscle dysfunction may occur in obesity. In fact, fatty infiltration with IMAT deposition and intracellular accumulation of lipids inside myocytes is commonly observed in obesity [ 30 , 31 ]. These alterations reduce muscle oxidative capacity while at the same time increasing anaerobic and glycolytic capacities and are responsible for metabolic dysfunction since they cause microinflammation, insulin resistance, and a decrease in the expression/activity of muscle LPL [ 32 , 33 , 34 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a matter of fact, metabolic muscle dysfunction may occur in obesity. In fact, fatty infiltration with IMAT deposition and intracellular accumulation of lipids inside myocytes is commonly observed in obesity [ 30 , 31 ]. These alterations reduce muscle oxidative capacity while at the same time increasing anaerobic and glycolytic capacities and are responsible for metabolic dysfunction since they cause microinflammation, insulin resistance, and a decrease in the expression/activity of muscle LPL [ 32 , 33 , 34 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, LPL activity in skeletal muscle negatively correlates with plasma insulin levels and could be lowered by insulin resistance [ 37 ]. A recent lipidomic study showed that higher VLDL and lower HDL concentrations were associated with higher muscle area, higher IMAT area, and lower IMAT density (an index of muscle fatty infiltration) [ 31 ]. Therefore, low HDL-cholesterol in patients living with obesity and with higher fat mass could simply be one of the consequences of the decrease in the insulin sensitivity of skeletal muscles caused by muscle fat infiltration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because adipose tissue depots were the outcome and physical activity was the main exposure of interest in our models, we did not adjust for BMI or waist circumference in our main models. Both BMI and waist circumference are common descendants of the adipose tissue depot outcomes [29] in this report, where adjusting for a common descendent can bias results [30]. We instead adjusted for height in our main models, that is, a measure of body size that is not a common descendent of the adipose tissue depot outcomes.…”
Section: Methodsmentioning
confidence: 99%
“…Physical activity is likely a common cause of the additional adipose tissue depots (e.g., visceral adiposity) and the adipose tissue depot outcome in the model. Specifically, the additional adipose tissue depots (e.g., visceral adiposity) are either [29]: (1) a common descendant of physical activity and not directly impacting the adipose tissue depot outcome examined in the model or (2) a mediator of the relationship between physical activity and the adipose tissue depot outcome in the model, where the incorrect inclusion of a mediator in the model will lead to an overadjustment bias [30].…”
Section: Methodsmentioning
confidence: 99%